PHILOSOPHICAL BASIS ON EDUCATION PRINCIPLE OF TAMANSISWA IN THE BEGINNING OF ITS ESTABLISHMENT - Bonifasia Ekta Fima Natalia (Academy of Education Journal, 2021)
This research aims to find the philosophical foundation of the article "Principles of Education of Tamansiswa at the Beginning of Its Establishment" in the book of "Ki Hajar Dewantara's Thought and Struggle" which is published by The National Awakening Museum of the Directorate General of Culture Ministry. This book consists of six parts, which discusses about some topics related to KHD. The researcher chose the second part to be analyzed because it discusses the teachings of KHD which is interesting and is relevant in recent education. The research method uses inferential content analysis. The researcher comprehend and interpret the symbolic message in the article. The research procedure used are the procurement of data, data reduction, inference, and data analysis. Construct analysis is done using qualitative approach with conceptual domain. Data validity was measured by using semantic validity and test retest reliability. The research result shows that there are philosophical basis on education principles of Tamansiswa, philosophy of essentialism and humanism, which is values ​​issued in cultural or social heritage that have existed since human civilization, for example in the among systems and trilogy leadership slogan Ing Ngarso Sung Tulodho, Ing Madyo Mangun Karso and Tut Wuri Handayani implemented in Tamansiswa education.